Forecasting zero U.S. nuclear history and the low probability of disarmament - Pearl, Jonathan (Strategic Studies Institute, U.S. Army War College, 2011)
A vigorous debate is occurring among American elites with respect to whether and when the United States should relinquish its nuclear weapons. Bolstering hopes for tangible results is that a U.S. President is again publicly and forcefully supporting disarmament. While this debate, which addresses both technical and political factors related to abolition, may be the most serious one of its kind since the dawn of the nuclear age, the future of U.S. nuclear weapons policy remains uncertain. The general approach advanced today in U.S. policy circles largely hews, after all, to the logic of the past 65 years: arms control and nonproliferation now, disarmament at an undetermined time in the future. Moreover, several conceptual and strategic barriers continue to block serious progress toward U.S. disarmament. By situating the current pro-disarmament rhetoric in this larger historical and strategic context, this monograph argues that there is reason to doubt whether the current push for disarmament will produce meaningful and lasting results